COLLECTIVE MEMORY âJUMâAT KELABUâ DI BANJARMASIN (PERSPEKTIF RESOLUSI KONFLIK ATAS PERISTIWA 23 MAY 1997) - Khotimah, Husnul (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2017)
This paper intends to explore the events of the conflict on 23 May 1997 from the aspect of the peaceful resolution. Where a peace-building effort is needed to maintain a peaceful situation. With the collective memory being represented in the present mass, it is part of the form of efforts in fostering post-conflict sustainable peace. Through the elements of society (Non-Governmental Actor) the memory of conflict is represented in the public sphere as a form of warning against forgetting over history.The role of a non-governmental actor in peacebuilding has a strategic role in resolving conflicts and building peace post-conflict. There are three things raised in this research that is: The incident of conflict "Jumat Kelabu" in the city of Banjarmasin in 1997, a collective memory form of conflict that built elements of society after the conflict, and the views of elements of society to the collective memory that was represented in the present in the effort to build peacebuilding. This research is a qualitative research, using a sociology-historical approach. The method used in data collection is through observation, interview, and documentation as secondary data. From the results of data analysis, the following results are obtained: the conflict that occurred in Banjarmasin city has a long chronology, the cause of this conflict is an unclear campaign route, the party base that controls Banjarmasin, because the mass of one the OPP that interfere with the Friday prayer, and aggressiveness of campaign participants. The form of peacebuilding efforts of the elements of society is to take peaceful action down the street, discussion/dialogue, and watching a documentary film. Elements of society argue that bringing back the memory of the conflict has two impacts: negative and positive impacts on peopleâs lives thereafter. These efforts need to be built to create an awareness that the conflict is painful, unpleasant and disturbing so hopefully it will never happen again.